Community Responses to Climate Change: Adaptive Practices in Coastal Villages of Java - Kharisma, Boby; Hanif (Mahogany Journal De Social, 2025)
Climate change poses a significant threat to Indonesia’s coastal communities as rising sea levels, coastal flooding, saltwater intrusion, and declining marine resources disrupt livelihoods and settlement security. Coastal villages in Java, characterized by dense populations and dependence on fisheries and agriculture, provide an important setting to understand local adaptive strategies. This study examines how these communities respond to climate pressures by integrating traditional knowledge, socio-cultural resilience, and institutional support. A qualitative case study design was combined with descriptive surveys involving 420 respondents in four villages. Data collection included semi-structured interviews, focus group discussions, household surveys, and field observations. Thematic analysis was used to interpret qualitative insights, while descriptive statistics illustrated major adaptation trends. Findings indicate that climate impacts are predominantly experienced through coastal flooding (72%), reduced fish catches (68%), and saltwater intrusion (61%). Common adaptation practices include mangrove planting (70%), adjusting fishing seasons (62%), and elevating houses (55%). Support from government and NGOs is visible in mangrove rehabilitation (65%) and preparedness training (58%), yet remains limited in financial assistance (40%) and access to climate information (45%). Overall, communities exhibit resilience rooted in solidarity and local wisdom, but adaptation is still hindered by economic constraints and insufficient long-term institutional support.